Characterization of ZnᵪCd₁ˍᵪS ternary semiconductor nanoparticles synthesized by microwave-assisted hydrothermal technique - Vernosfaderani, Mina Askari (2014)
In this work, the microwave-assisted hydrothermal method was used to synthesize ZnxCd1-xS ternary quantum dots. In order to study the effect of different stoichiometries on ZnxCd1-xS properties, the molar ratio of Zn/Cd was chosen as 0.1/0.9, 0.3/0.7, 0.5/0.5, 0.7/0.3, and 0.9/0.1, and to use semiconductor quantumdots in technology, the stability of these materials is very important and can achieve by capping the particles with either organic or inorganic materials like polymers. Zinc chloride (ZnCl2), cadmium chloride (CdCl2), and sodium sulfide (Na2S) were used as Zn, Cd, and S sources respectively, and polyvinylpyrrolidone (PVP) and thioglycolic acid (TGA) were used as capping agent and stabilizer to control particle’s growth and distill water as a solvent. The solution was heated in a microwave oven with 100% power for 4 minutes and the resulting precipitation was centriguged, washed, and dried at 100 ºC for 24 hours. By increasing the value of x from 0.1 to x=0.9, the powder color changed from dark yellow to white as verified by X-ray diffraction (XRD). The average particle sizes of ZnxCd1-xS nanoparticles as deduced from Sherrer’s equation by XRD peaks and from the images of transmission electron microscopy (TEM) were found to vary within range 3-5 nm with x values. The optical band gap energy in the range of 2.3 to 2.93 ev was calculated by Tauc plot of the UV-visible spectra. The band gap has increased with increasing the value of x due to a decrease in particle size. The synthesized Zn0.9Cd0.1S quantum dots capped by TGA and PVP have band gaps between 2.93 to 3.43, and 2.91 to 2.98 respectively. PL spectra for ZnxCd1-xS have three emission peaks related to sulfur, zinc, and cadmium vacancies respectively. The emission peaks II that are belong to zinc vacancies are observed at 484, 483, 483, 481, and 478 that are shifted to the lower wavelengths by increasing the value of x, and correspond to 2.56, 2.57, 2.57, 2.58, and 2.6 (eV). This significant continuous shift is an evidence for the formation of the ternary ZnxCd1-xS quantum dot, rather than forming separate CdS, ZnS, or core-shell nanoparticle structure.